Protective Paternalism: Understanding the Hidden Face of Sexism in Politics - Edwards, Margaret F. (Tufts Archival Research Center, 2020)
Research following the 2016 U.S. presidential election challenges the idea that gender prejudice does not impact voting behavior. Since 2016, researchers have found that hostile sexism, beliefs predicated upon the inferiority of women, correlates to educational attainment and party affiliation. However, these studies do not focus on how benevolent sexism, a set of beliefs predicated upon protective paternalism and chivalry, relate to political attitudes and behavior. In this paper, I demonstrate that hostile and benevolent sexism are uncorrelated. While adherence to hostile sexism correlates with educational attainment and party affiliation, benevolent sexism is uncorrelated to such social sorting. Using the Ambivalent Sexism Inventory and socio-demographic questions on a nationally representative dataset of 993 people, I find that adherence to benevolent sexism is widespread with one exception: college educated females. While we assume large portions of the general population express low levels of sexism, only 26.85% of individuals reject both benevolent and hostile sexism. Notably, this rejection of sexism increases more than twofold amongst college educated women. This finding helps explain why it has proven so challenging to garner the support necessary to elect female candidates.; Advisors: Professor Eitan Hersh and Professor Brian Schaffner